Employability and job search behavior: A six-wave longitudinal study of Chinese university graduates. Issue 2 (13th February 2017) - Yizhong, Xie; Lin, Zhibin; Baranchenko, Yevhen; Lau, Chi Keung; Yukhanaev, Andrey; Lu, Hailing
Abstract : Purpose: Graduate employability is a key concern for many observers particularly at a time when education is increasingly available for the masses. The purpose of this paper is to examine the impact of graduate perceived employability on job search by integrating theory of planned behavior and to identify how job search self-efficacy, subjective norms, intention and intensity change over time. Design/methodology/approach: Data were collected from a six-wave survey study with a sample of Chinese university graduating students. Findings: Results show that perceived employability has a positive and significant effect on job search self-efficacy, attitude, intention and intensity; and that all the repeated measuring variables (except job search attitude) decreased over time. Practical implications: The study is useful for educators, employers and prospective students. It prompts discussion of reforms in the curriculum to increase graduate awareness of the complexity of the job search process and existing opportunities. The study could also help to explain how job search behavior changes over time. Originality/value: The findings carry implications for both higher education research and the measures of improving graduate employability. The study fills the gap in the literature by integrating employability and the theory of planned behavior into one framework in order to analyze the process of Chinese university graduates' job search behavior.